Use of methotrexate in an exuberant case of confluent and reticulated papillomatosis of Gougerot and Carteaud in a teenager, - Alexandra Brugnera Nunes de Mattos; Carolina Finardi Brummer; Gabriella Di Giunta Funchal; Daniel Holthausen Nunes (Sociedade Brasileira de Dermatologia, 2020)
Abstract Confluent and reticulated papillomatosis of Gougerot and Carteaud is a rare dermatosis with onset during puberty, more prevalent in females than in males. The pathogenesis is unknown, but some theories suggest either a keratinization or endocrine disorder. The lesions are verrucous, brownish, hyperkeratotic papules or spots that coalesce in a confluent and/or reticulated pattern. This report presents a case with extensive cutaneous involvement associated with acanthosis nigricans and good response to treatment with methotrexate.